Determinants of Tax Compliance Behaviour among Rental Income Earners in Pokhara - Tiwari, Ghanashyam (Journal of Nepalese Business Studies, 2021)
Rental tax is an important source of revenue for local government units. After Nepal adopted fiscal federalism, concerns have been shown by policymakers as well as academicians on the fiscal sustainability of the local government units. In this context, this study attempts to explore tax compliance behaviour among rental income owners in Pokhara. The study is based on a survey of 196 households located in wards 9, 11 and 17 of Pokhara Metropolitan City. The wards represent commercial, semi-urban, and densely populated areas of the city respectively. The required data were gathered employing a self-administered questionnaire comprising Likert scales to measure tax awareness, attitude towards tax, cost of non-compliance, peer influence for compliance, government incentives, and tax compliance behavior of the rental income earner. The data collected were analyzed employing ANOVA, correlation and multiple regression. The research revealed a positive relationship between tax awareness, attitude towards tax, peer influence, and government incentives with tax compliances. The study findings depict that the taxpayers’ awareness and perception towards tax are important variables that affect the compliance behavior of rental taxpayers. Moreover, the results reveal that the rental income earner in Pokhara does not comply with the tax rules due to the lower cost of non-compliance as negative relationship established was found between tax compliance and the cost of non-compliance. Metropolitan tax authority needs to focus on awareness and government incentives rather than the cost of non-compliance for better adherence to tax rules among rental taxpayers.